Protist-Bacteria Associations: Gammaproteobacteria and Alphaproteobacteria Are Prevalent as Digestion-Resistant Bacteria in Ciliated Protozoa - Gong, Jun; Qing, Yao; Zou, Songbao; Fu, Rao; Su, Lei; Zhang, Xiaoli; Zhang, Qianqian (Frontiers in Microbiology, 2016)
Protistan bacterivory, a microbial process involving ingestion and digestion, is ecologically important in the microbial loop in aquatic and terrestrial ecosystems. While bacterial resistance to protistan ingestion are relatively well understood, little is known about protistan digestion in which some ingested bacteria could not be digested in cells of major protistan grazers in the natural environment. Here we report the phylogenetic identities of digestion-resistant bacteria (DRB) that could survive starvation and form relatively stable associations with 11 marine and one freshwater ciliate species. Using clone library and sequencing of 16S rRNA genes, we found that the protistan predators could host a high diversity of DRB, most of which represented novel bacterial taxa that have not been cultivated. The localization inside host cells, quantity, and viability of these bacteria were checked using fluorescence in situ hybridization. The DRB were affiliated with Actinobacteria, Bacteroidetes, Firmicutes, Parcubacteria (OD1), Planctomycetes, and Proteobacteria, with Gammaproteobacteria and Alphaproteobacteria being the most frequently occurring classes. The dominance of Gamma- and Alphaproteobacteria corresponds well to a previous study of Global Ocean Sampling metagenomic data showing the widespread types of bacterial type VI and IV secretion systems (T6SS and T4SS) in these two taxa, suggesting a putatively significant role of secretion systems in promoting marine protist-bacteria associations. In the DRB assemblages, opportunistic bacteria such as Alteromonadaceae, Pseudoalteromonadaceae and Vibrionaceae often presented with high proportions, indicating these bacteria could evade protistan grazing thus persist and accumulate in the community, which, however, contrasts with the well-known rarity of these bacteria in nature. This begs the question whether viral lysis is significant in killing these indigestible bacteria in microbial communities. Taken together, our study on the identity of DRB sheds new light on microbial interactions and generates further hypothesis on the potential importance of bacterial protein secretion systems in structuring bacterial community composition and functioning of “microbial black box” in aquatic environments.